Peranan Yesus sebagai Guru dalam Kehidupan Umat Perjanjian Baru - Philipus Benitius Metom (JURNAL PROPHETA, 2023)
The New Testament Scriptures write about Jesus who always taught those who believed in Him. He taught through the word and sermons. He proved his teachings by healing the sick and disabled, by feeding the hungry and by expelling demons from the possessed. Because his education and teaching were of interest to a large number of students, eventually there were also titles given to him as teacher and it was not uncommon for people to address him as Rabbi. This prompted the author to find out about Jesus' title as Teacher and Rabbi given by the students he educated and taught by asking problematic questions, namely: Why was Jesus given the title as Teacher? What is the role of Jesus as Teacher in the lives of the New Testament people? The answers to these two questions will be sought by looking at a number of literature references to find out the role of Jesus as Teacher for the New Testament people and at the same time to find out the reasons for giving Him this title